Face 2 Face Upper Intermidiate. Students Book - Redston, Chris and Cunnigham Gillie (Cambridge Cambridge University Press, 2007)
Face 2 Face is a generaly English course for adults and young adults who want to learn to communication quickly and effectively in todays world. Based on the communicative approach, it combines the best in current methodology with special new features designed to make learning and teaching easier. Vocabulary and grammar are given equal importance and there is a strong focus on listening and speaking in social situations.
Keywords: English Practice